Electrochemical degradation and mechanistic analysis of microcystin‐LR. Issue 8 (1st February 2013) - Zhang, Yanrong; Zhang, Ying; Yang, Nan; Liao, Wenjuan; Yoshihara, Sachio
Abstract Background Microcystin‐LR (MC‐LR) is very stable under natural sunlight and resistant to high temperatures and UV radiation. Conventional treatment techniques are found to be inefficient in removing these toxins from potable water systems. Advanced oxidation technologies (AOTs) are considered a promising technique for the destruction of microcystins. Among the various AOTs, electrochemical oxidation (EO) has been proved to be very successful in degrading the organic pollutants. The purpose of this study was therefore, to determine the feasibility of MC‐LR removal and its mechanism by EO. The effect of operational parameters on the degradation efficiency of MC‐LR has been studied. Results The degradation of MC‐LR followed a pseudo‐first‐order kinetic with a rate constant (k1) of 0.017 min−1. Current density and electrolytes can affect the degradation rate; the pH of the different anionic solutions had a negligible effect on the degradation of MC‐LR. The destruction of the key functional groups of MC‐LR effectively inhibits its toxicity, which is confirmed by toxicity tests. Conclusion The results demonstrated the feasibility of electrochemical oxidation on boron‐doped electrode for the removal of MC‐LR from the aquatic environment. © 2012 Society of Chemical Industry